Balancing National Sovereignty: The Impact of Bilateral Investment Treaties on Contemporary Islamic Economic Law - Rana Saad Shakar; Mohammed Faroq Mahmood; Nibras Arif Abdulameer; Zahraa Mahdi Dahash; Iskaliev Azat (Faculty of Sharia, IAIN Metro, 2025)
Bilateral Investment Treaties (BITs) play a crucial role in shaping global investment flows, but their impact on national sovereignty and economic policy remains a subject of ongoing debate, particularly within the framework of contemporary Islamic economic law. This study addresses a critical gap in the literature by examining how BITs influence regulatory autonomy in nations that adhere to Islamic economic principles. Using a mixed-methods approach, it analyzes quantitative data on Foreign Direct Investment (FDI) flows from UNCTAD and the World Bank, alongside qualitative case studies of developing countries navigating BITs within Islamic legal frameworks. From a contemporary Islamic economic law perspective, BITs should align with Shariah principles, including economic justice, Maslahah (public interest), and the prohibition of Riba (usury) and Gharar (uncertainty). However, while BITs can enhance FDI inflows and create a more predictable investment climate, they often restrict national policy flexibility, particularly through Investor-State Dispute Settlement (ISDS) mechanisms, which may limit government control over critical sectors such as public health, environmental protection, and taxation. This research contributes to the academic discourse by integrating contemporary Islamic economic law into BIT analysis, highlighting the need for treaty reforms that uphold national sovereignty while fostering ethical and sustainable investment. By exploring the intersection of international investment law and Islamic economic values, this study provides valuable insights for policymakers seeking to balance economic growth with social welfare and long-term development in line with Islamic principles.